Effect of AlGaN interlayer in bottom quantum barriers on efficiency enhancement of InGaN green light-emitting diodes. (April 2019) - Wang, Zhenxu; Mo, Chunlan; Zheng, Changda; Wu, Xiaoming; Liu, Junlin; Jiang, Fengyi
Abstract: The effect of AlGaN interlayer (IL) in bottom quantum barriers on efficiency enhancement of the InGaN green light-emitting diodes (LEDs) on patterned silicon substrate has been investigated. Significantly, the LEDs with AlGaN IL show high emission efficiency at low current and the maximum wall-plug efficiency is 58% at 7.5 mA (17 mW). This is attributed to the effect of AlGaN IL on carrier distribution and screening dislocations due to its higher bandgap, based on LEDs structure with V-shaped pits. Consequently the ameliorated properties of LEDs with AlGaN IL provide a good choice for LEDs operating at low current density. Hightlights: The use of AlGaN interlayer in GaN barriers. Significant efficiency enhancement of green LEDs at low current. The reduction of operating voltages. The investigation of carrier transport in green MQWs with V-shape pits.